Effect of Light Intensity on Zebra Fish (Danio rerio) Cell Regeneration - Darniwa, Adisty Virakawugi; Cahyanto, Tri; Rahayu, Savira Ngesti (Jurnal Pijar Mipa, 2024)
Zebrafish (Danio rerio) is one of the model animals in cell regeneration studies because it has a high ability to regenerate tissue structures, one of which is its caudal fin. This study was conducted to determine the different light interventions on the regeneration of the caudal fin of zebrafish. The research method used is an experimental study with the observed parameters, including specific growth, absolute weight gain, length increase, and survival. A total of 28 male wild-type zebrafish were used in this study at the age of 3 months. The amputated zebrafish on its caudal fin was placed at different light intensities (control, 0 lux, 60 lux, and 90 lux). Parameter measurements were carried out every two days. ANOVA analyzed the data obtained with a significance level of 95%. The results showed that at a light intensity of 90 lux, the zebrafish tail fin regeneration was the most significant based on an increase in total length of 0.10 mm. Using a light intensity of 90 lux is the best condition in the regeneration process of the zebrafish caudal fin. The research findings could be further applied in the healing process of external wounds.